PERAN MA TA PELAJARAN PKN SD SEBA GAi W AHANA PENDIDIKAN HUKUM BAGI ANAK - Sekar Purbarini Kawuryan (MAJALAH ILMIAH PEMBELAJARAN, 2007)
It is necessary lo grow the awareness that there is norm that controland guide individual behavior in social life since childhood Civiceducation is a subject in elementary school that is closely related tolaw and civic. This subject is expected to help students to be awareof law and conslilulion.Law related education in school is supposed lo be in/ended forhelping studenls gain knowledge and skill necesswy so thal lhey caneffectively participale in law organizalions. Law education inelemenlary school cannot be alienated from student's moraldevelopmenl. Law education learning model in elementary schoolshould be atfjusted lo children's thinking ability and moraldevelopmenl.